Flood risk assessment and territorial planning in the playas canton - Cedeño, Alexandra (Artes: Architecture, Technology and Sustainability, 2022)
The General Villamil Playas canton suffers every year from floods in some neighborhoods and proportions, in some places, especially in informal settlements and high-risk sites. Over the years, it increases with each winter season instead of diminishing the threat, especially in years corresponding to the El Niño phenomenon. The PDOT 2019 – 2023 of the Playas canton identifies the risks in the territory without evaluating the specific places and the levels of risk. This research applies the method developed by the National Secretariat for Risk and Emergency Management (SNGRE) in the Playas canton. The methodology was used to assess the risk of flooding due to extreme rainfall and the arrival of a tsunami. As a result, this canton has a medium risk level for floods caused by extreme rainfall and a high-risk level in the presence of a tsunami.
Keywords: Risk; Threat; Floods; Extreme precipitation